Effect of replacing dicalcium phosphate with mono-dicalcium phosphate to supplement phosphorus on laying performance, phosphorus-calcium metabolism and bone metabolism of aged laying hens - Ren, Yuechang; Zhao, Tianyu; Zhang, Kaiying; Zhu, Zhengqi; Li, Linkui; Li, Yang; Jiang, Shuzhen; Jiao, Ning; Yang, Weiren (Frontiers in Veterinary Science, 2023)
The objective of this study was to evaluate the effect of replacing dicalcium phosphate (DCP) with mono-dicalcium phosphate (MDCP) to formulate low-phosphorus (P) diets on laying performance, egg quality, phosphorus-calcium metabolism, and bone metabolism of 69–78- week-old aged laying hens. Hy- Line Brown laying hens (n = 1350, 69 weeks old) were randomly assigned to six treatments, each with five replicates of 45 hens. The control group (CON) was supplemented with DCP inorganic phosphorus (Pi) at the NPP level of 0.20% (dietary NPP level of 0 .32%). Test groups (T1–T5) were supplemented with MDCP Pi at NPP levels of 0.07%, 0.11%, 0.15%, 0.18%, and 0.20% (dietary NPP levels of 0.19%, 0.23%, 0.27%, 0.30%, and 0.32%, respectively) . When supplemented with 1470 FTU/kg phytase, extra DCP Pi or MDCP Pi did not affect (P > 0 .05) laying performance, egg quality, or serum P and Ca levels . The tibia breaking strength was significantly higher (P < 0 .05) in the 0.18% and 0.20% NPP MDCP Pi groups than in the 0.20% NPP DCP Pi group . The breaking strength, Ca content, and P content of tibia in 0.11% and 0.15% NPP MDCP Pi hens were not significantly (P > 0 .05) different from those in 0.20% NPP DCP Pi hens. Hens fed 0 .07% NPP MDCP Pi had higher (P < 0 .01) serum levels of osteoprotegerin ( OPG), type-I collagen c-telopeptide (CTX-I), and tartrate-resistant acid phosphatase 5b (TRACP-5b) than those in all other groups. Serum levels of TRACP-5b and CTX-I in the 0 .11% and 0 .15% NPP MDCP Pi group were significantly lower than those in 0.18% and 0.20% NPP MDCP Pi groups and the 0.20% NPP DCP Pi group (P < 0 .0001). The expression of P transporters type IIa Na/Pi cotransporter (NaPi-IIa) in 0.11% and 0.15% NPP MDCP Pi hens were higher than those in 0.20% NPP MDCP Pi group and 0.20% NPP DCP Pi group (P < 0 .0 5 ). In summary, when MDCP was used instead of DCP to supplement P, NPP levels could be reduced to 0.11% (dietary NPP level of 0.23%).